Pengembangan Kapasitas Kelompok MASTALI MADU Dalam Menjaga Ekosistem Mangrove di Kelurahan Purnama Kota Dumai - Mandar, Agus; Yunus, Wan Muhammad; Asfar, Ali (Universitas Riau, 2024)
Damage to mangrove ecosystems due to abrasion and deforestation has affected the community, especially those who have a livelihood as traditional fishermen because of the decline in their catch from an average of 50 kg per day to 20 kg per day. This condition has raised the awareness of the local community to protect the mangrove ecosystem by forming the Pokmaswas Masyarakat Tangguh dan Peduli Mangrove Dumai (MASTALI MADU). However, in carrying out its activities there are various challenges and obstacles due to limited abilities, knowledge, infrastructure and budget support. This research aims to develop the capacity of Pokmaswas MASTALI MADU in the form of 1) Individual capacity development, 2) Organizational management, 3) Facilities and infrastructure, and 4) group operational budget support. To develop the capacity of Pokmaswas, the support and role of relevant stakeholders such as BRGM, Riau Province LHK Office, Dumai City Government, PT Pertamina Hulu Rokan, and Riau University as the supervising university are needed. The synergy of all these components is expected to strengthen the Capacity Development of Pokmaswas MASTALI MADU in maintaining the mangrove ecosystem in a sustainable manner.